FDG‐PET/CT detection of very early breast cancer in women with breast microcalcification lesions found in mammography screening. Issue 4 (14th April 2015) - Peng, Nan‐Jing; Chou, Chen‐Pin; Pan, Huay‐Ben; Chang, Tsung‐Hsien; Hu, Chin; Chiu, Yu‐Li; Fu, Ting‐Ying; Chang, Hong‐Tai
Abstract: Introduction: To assess the efficacy of positron emission tomography/computed tomography with the glucose analogue 2‐[ 18 F]fluoro‐2‐deoxy‐D‐glucose (FDG‐PET/CT) in Taiwanese women with early breast cancer detected by mammography screening. Methods: Dual‐time‐point imaging of whole‐body supine and breast prone scans using FDG‐PET/CT were performed sequentially in the pre‐operative stage. Results: A total of 11, 849 patients underwent screening mammography, of whom 1, 209 (10.2%) displayed positive results. After further investigation, 54 patients underwent FDG‐PET/CT. Post‐operative pathology examinations revealed malignancies in 26 lesions, including invasive breast cancer in 11 cases and non‐invasive breast cancer in 15 cases, as well as benign disease in 30 lesions. The FDG‐PET/CT findings from the whole‐body scans were positive for 9 of 11 invasive breast cancers (81.8%) and 3 of 15 non‐invasive cancers (20%), and they were negative for all benign lesions. The sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) of FDG‐PET/CT with whole‐body supine imaging were 46.2%, 100%, 100% and 68.2%, respectively. Breast prone imaging revealed another patient with ductal carcinoma in situ, increasing the sensitivity to 50%. Importantly, positive PET findings were significantly correlated with tumour histology ( P  = 0.006), tumour size ( P  = 0.039) and Ki‐67 expression ( P  = 0.011). Conclusions: FDG‐PET/CT with whole‐body scanning demonstrated high sensitivity to invasive breast cancer, limited sensitivity to non‐invasive breast cancer, and high specificity for breast cancer. FDG‐PET/CT might be useful for differentiating tumour invasiveness. However, the good PPV but poor NPV do not allow the physician to discard the biopsy.